FACTORS INFLUENCING STUDENTS' INTENTION TO ENROLL IN BACHELOR OF ACCOUNTING DEGREE: AN APPLICATION OF THEORY OF REASONED ACTION - Zainin Bidin; Hasnah Haron; Yuserrie Zainuddin; Ishak Ismail (EKUITAS (Jurnal Ekonomi dan Keuangan), 2005)
The accounting profession in Malaysia is facing a dilemma. The demand for accountants in this country is higher than the number of accountants that can be produced. In order to attract more students to this field, factors influencing their intention to choose, must be identified. This study tries to identify the factors influencing student's intention to enroll into a Bachelor of Accounting degree. The Theory of Reasoned Action developed by Ajzen and Fishbein was used as the framework. One hundred and seventy three (173) students from public and private higher learning institutions in Penang and Kedah took part in this study. The results showed that personal beliefs of the students were the main influence his attitude to choose. Pressures from peers and lecturers were also seemed to be important factors that the student considers in making his or her decision